Designs of concrete mixes with compression resistance as a 210 kg/cm2; using the method of A.C.I and materials used in Arequipa - Miguel Renato Díaz Galdos (2019)
As a result of a diverse and continuous verification executed in building constructions of single family home in Arequipa city, we could determine important findings: concrete mixtures are performed without any type of professional assessment, and in addition to this, without performing accurate measurements of component proportions, and without taking into account the source of the materials involved. In order to obtain a concrete compressive strength equal to 210 Kg/zm2 at the time of 28 days, the ACI Method of Concrete Mix Design was applied on Yura IP Cement, tap water from La Tomilla Water Plant — SEDAPAR, materials of greater use and consumption in Arequipa City, to perform a comparative study on concrete mixtures design. The materials used in this study such as: coarse and fine aggregate were taken and obtained from local quarries from Arequipa: Cono Norte, Chiguata y Alto San Martin. Testing final results were obtained from the aggregate physical properties and concrete trials and tests in fresh and hardened conditions were all performed at the Laboratories of Concrete of the Civil Engineering Professional and Environment Program of the Universidad Católica de Santa María. The physical properties of cement and potable water were obtained from Cemento Yura Company, and SEDAPAR (Water and sewer utilities in Arequipa.) After performing an accurate testing and regulatory trials of the aggregates and rigorous analysis of the components and concrete mixtures designs, we may conclude and state that concrete proportions and characteristics of the materials components differ according to the source of the aggregates involved.